Wear-resistant polyurethane tire and method of making same

CN122685847BActive Publication Date: 2026-10-27NANTONG HUIHONG REHABILITATION EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611187386.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-27
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

[0004]为了解决现有技术中聚氨酯实心轮胎在重载工况下耐磨性能与耐疲劳性能不足、动态生热偏高的问题,本申请提供一种耐磨聚氨酯轮胎及其制备方法

Benefits of technology

[0047]1、由于本申请采用生物基聚醚多元醇为基体,搭配共价杂化补强填料与分级动态扩链体系,配合金属配位交联助剂构建双层级交联网络,通过共价键强化填料与基体的界面结合,依托分级键能有序耗散交变应力,在维持基础承载能力的同时,提升材料的耐磨性能与抗裂纹扩展能力,改善动态载荷下的生热表现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685847B_ABST
    Figure CN122685847B_ABST
Patent Text Reader

Abstract

The application relates to the polyurethane tire manufacturing technical field, and particularly discloses a wear-resistant polyurethane tire and a preparation method thereof. The tire is formed by mixing, cross-linking, foaming and curing of A and B components, the A component comprises a bio-based polyether polyol, a covalent hybrid reinforcing filler, a hierarchical dynamic chain extender, a metal coordination cross-linking aid, a solid lubricating filler, a slow-release interface repair microsphere, a catalyst and a compound foaming agent; and the B component is an aliphatic isocyanate prepolymer. The preparation method comprises the following steps: after the filler is dried, the polyol is pre-dispersed, the remaining aids are added and mixed and defoamed, the B component is preheated and defoamed, high-speed mixing is carried out, and then the tire is molded, low-pressure pressure maintaining is carried out, three-stage gradient temperature rising cross-linking and foaming are carried out, the tread is heated in a partitioned manner in a medium-high temperature stage to form component gradient enrichment, demolding and curing are carried out, and the tire is obtained. The tire has the properties of high wear resistance, crack propagation resistance and self-repairing performance through the synergy of covalent interface combination and hierarchical dynamic cross-linking, the tread has high wear resistance and the tire body has high resilience, and the process is simple and suitable for industrialized production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polyurethane tire manufacturing technology, and more specifically, to a wear-resistant polyurethane tire and a method for preparing the same. Background Technology

[0002] Polyurethane solid tires, with their airless structure, strong puncture resistance, and stable load-bearing performance, are widely used in warehousing and logistics equipment, industrial handling vehicles, and special-purpose machinery. They provide stable support for equipment in complex road conditions, reduce daily maintenance costs, and improve the safety and continuity of operations. Currently, most conventional polyurethane solid tires use a formulation system of polyols and isocyanate matrices combined with reinforcing fillers, and are manufactured through a one-time cross-linking and curing process. This mature manufacturing process can meet the basic usage requirements of ordinary working conditions.

[0003] However, under long-term heavy-load conditions, existing polyurethane tires still have certain performance shortcomings. Their reinforcing fillers are mostly dispersed in the matrix through physical blending, resulting in weak interfacial bonding between the filler and the matrix, a relatively simple cross-linked network structure, limited stress dissipation capacity under alternating loads, and a tendency for microcrack initiation and propagation. At the same time, the internal heat generated during dynamic operation is relatively high, which to some extent restricts the tire's wear resistance and fatigue life, making it difficult to adapt to more demanding operating scenarios. Summary of the Invention

[0004] To address the issues of insufficient wear resistance and fatigue resistance, and excessive dynamic heat generation in existing polyurethane solid tires under heavy load conditions, this application provides a wear-resistant polyurethane tire and its preparation method.

[0005] In a first aspect, this application provides a wear-resistant polyurethane tire, which adopts the following technical solution:

[0006] A wear-resistant polyurethane tire is made by mixing, cross-linking, foaming and curing A polyol composite component and B isocyanate prepolymer component in a mass ratio of 100:32 to 100:40.

[0007] The A polyol composite component comprises, by weight, 75-90 parts of bio-based polyether polyol matrix, 8-18 parts of covalent hybrid reinforcing filler, 3-7 parts of hierarchical dynamic chain extender, 0.4-1.0 parts of metal coordination crosslinking aid, 0.3-1.2 parts of solid lubricating filler, 0.2-0.8 parts of slow-release interface repair microspheres, 0.2-0.6 parts of catalytic component, and 1-3 parts of compound foaming system;

[0008] The B isocyanate prepolymer component is an aliphatic isocyanate prepolymer.

[0009] By employing the above technical solutions, bio-based polyether polyols and aliphatic isocyanate prepolymers crosslink to form a polyurethane main network, providing the tire with a foundation for elasticity and weather resistance. Covalently hybridized reinforcing fillers are chemically bonded to the matrix, eliminating the interfacial slippage and stress concentration defects common in physically blended fillers, thus improving wear resistance and mechanical strength. A hierarchical dynamic chain extender simultaneously introduces hindered urea covalent dynamic bonds and urea supramolecular hydrogen bonds into the polymer main chain. The hindered urea bonds undergo reversible fracture at the high-stress zone at the microcrack tip to dissipate energy, while the hydrogen bonds provide secondary energy dissipation and drive network rearrangement and repair. Combined with metal coordination crosslinking aids, this forms a dynamic crosslinking network with progressively increasing bond energy, effectively delaying microcrack propagation and endowing the material with self-healing capabilities. Solid lubricating fillers form micro-friction-reducing points at the tread friction interface, reducing abrasive and adhesive wear. Slow-release interfacial repair microspheres release coated coupling agents during the molding stage, performing in-situ repair of weak points at the filler-matrix interface. The synergistic effect of the various functional components gives the tire high wear resistance, crack propagation resistance, and good dynamic fatigue performance.

[0010] Preferably, the covalent hybrid reinforcing filler is a hindered phenol-supported silane covalently grafted lignin-nano silica hybrid filler, with alkali lignin as the base, and Si-OC covalently bridged structure formed with fumed nano silica through an epoxy silane coupling agent, and the mass ratio of alkali lignin to fumed nano silica is 2:1 to 4:1.

[0011] The graded dynamic chain extender is a compound of N,N'-di-tert-butylethylenediamine and N,N'-di(2-hydroxyethyl)urea;

[0012] The sustained-release interface repair microspheres are polylactic acid sustained-release microspheres, which are internally coated with γ-glycidoxypropyltrimethoxysilane, and the microsphere particle size is 10 μm to 30 μm.

[0013] By adopting the above technical solution, the covalent hybrid reinforcing filler uses alkali lignin as the organic framework. The epoxy groups of the epoxy silane coupling agent react with the phenolic hydroxyl groups of lignin through ring-opening reaction, and after the methoxy groups are hydrolyzed, they condense with the silanol groups on the surface of nano-silica to form an organic-inorganic hybrid structure with Si-OC covalent bonds. The flexible organic phase of lignin can generate micro-area deformation to buffer stress when subjected to force, while the rigid phase of nano-silica provides high hardness support. The two achieve a balance between rigid wear resistance and flexible buffering through covalent bonds. At the same time, the hindered phenolic antioxidant is loaded in situ in the gaps between lignin molecules, which is not easy to migrate and lose, thus achieving long-term anti-aging. In the hierarchical dynamic chain extender, the secondary amino group of N,N'-di-tert-butylethylenediamine reacts with isocyanate to form sterically hindered urea bonds. The large steric hindrance of the tert-butyl group makes this bond stable at room temperature, but it preferentially responds to the energy dissipation of fracture under stress concentration. The urea groups of N,N'-bis(2-hydroxyethyl)urea form a supramolecular hydrogen bond network. The hydrogen bond breakage-recombination rate is higher than that of the hindered urea bonds, and the network integrity can be quickly restored after stress relief. The bond energies and response rates of the two dynamic bonds are different, forming a hierarchical and ordered energy dissipation and repair mechanism. The slow-release interface repair microspheres use polylactic acid as the shell and γ-glycidoxypropyltrimethoxysilane as the core material. During the medium- and high-temperature crosslinking foaming stage, the polylactic acid shell is thermally degraded, and the released coupling agent diffuses to the filler-matrix interface. Its epoxy groups react with the residual phenolic hydroxyl groups of lignin, and after the methoxy groups are hydrolyzed, they condense with the hydroxyl groups on the silica surface, performing secondary covalent repair on interface bonding defects and improving the overall integrity of the material.

[0014] Preferably, the metal coordination crosslinking aid is selected from at least one of zinc acetylacetonate, zirconium acetylacetonate, and aluminum acetylacetonate;

[0015] The solid lubricating filler is selected from at least one of oleic acid-coated nano molybdenum disulfide and polytetrafluoroethylene micro powder.

[0016] The catalytic component is an organic bismuth catalyst, selected from at least one of bismuth neodecanoate and bismuth isooctanoate;

[0017] The compound foaming system is composed of water and cyclopentane;

[0018] The bio-based polyether polyol matrix is ​​a castor oil-modified polyol with a hydroxyl value of 320 mg KOH / g to 360 mg KOH / g.

[0019] By adopting the above technical solution, metal coordination crosslinking aids such as zinc acetylacetone form reversible coordination bonds with lignin phenolic hydroxyl oxygen atoms and tertiary amine nitrogen atoms in hierarchical dynamic chain extenders through metal ions. The bond energy is between hindered urea covalent bonds and supramolecular hydrogen bonds, further enriching the bond energy hierarchy of the dynamic network. This allows the material to respond and dissipate energy in a graded manner under different stress levels. At the same time, these coordination bonds play an auxiliary bridging role between the filler and the matrix. The oleic acid carboxyl groups on the surface of nano-molybdenum disulfide coated with oleic acid can coordinate with the metal ions of the metal coordination crosslinking aid, integrating the lubricating filler into the dynamic auxiliary network. During friction, the nano-molybdenum disulfide particles fill the micro-pits on the tread, reducing abrasive wear. The oleic acid coating layer improves its compatibility with the polyurethane matrix, preventing the formation of a continuous lubricating film on the macroscopic surface, which would affect grip. Organobismuth catalysts exhibit high selectivity for the gelation reaction of isocyanates and hydroxyl groups, but low catalytic activity for the foaming reaction of isocyanates and water. This makes it easier to control the rate matching between the crosslinking and foaming reactions, preventing excessively rapid foaming that could lead to cell merging or collapse. In the water-cyclopentane composite foaming system, water reacts with isocyanates to generate carbon dioxide, which acts as a chemical foaming agent, while cyclopentane undergoes physical foaming through heating and vaporization in the low-temperature interfacial reaction zone. The sequential foaming functions of both at different temperature ranges are beneficial for forming a uniform microporous structure, achieving both lightweighting and shock absorption. Castor oil-modified polyols, derived from renewable resources, provide segmental flexibility and hydrophobicity through their long fatty acid chains, helping to reduce internal heat generation and dynamic friction coefficients within the system.

[0020] Preferably, the aliphatic isocyanate prepolymer is a terminal isocyanate prepolymer obtained by reacting 4,4'-dicyclohexylmethane diisocyanate with polyether polyol, and its NCO mass fraction is 16% to 19%.

[0021] By adopting the above technical solution, 4,4'-dicyclohexylmethane diisocyanate has a saturated aliphatic structure and does not contain easily oxidized chromogenic groups such as benzene rings. The polyurethane generated by the reaction of the prepolymer with castor oil-modified polyol is less prone to yellowing during long-term outdoor use and exhibits better UV aging resistance than aromatic isocyanate systems. The NCO mass fraction of the prepolymer is controlled within a suitable range, ensuring good fluidity at the casting temperature. After mixing with component A, the crosslinking reaction is stable and controllable, which is beneficial for the uniform curing degree of the inner and outer layers of thick-walled tire products.

[0022] Secondly, this application provides a method for preparing a wear-resistant polyurethane tire, employing the following technical solution:

[0023] A method for preparing a wear-resistant polyurethane tire includes the following steps:

[0024] S1. Drying treatment of filler: The covalent hybrid reinforcing filler is vacuum dried under heating conditions, and then sealed and stored for later use.

[0025] S2 and A material homogenization preparation: According to the formula ratio, the bio-based polyether polyol matrix and the dried covalent hybrid reinforcing filler are pre-dispersed first, then the graded dynamic chain extender, metal coordination crosslinking aid, solid lubricating filler, slow-release interface repair microspheres and catalytic components are added and dispersed until uniform. Finally, the compound foaming system is added and mixed evenly. After heating, vacuum degassing is performed and the mixture is kept warm for later use.

[0026] S3, B material preheating and degassing: The aliphatic isocyanate prepolymer is preheated and stirred, then vacuum degassed;

[0027] S4. Mixing, Injection and Closure: Mix and stir the heat-insulated component A and component B according to the set mass ratio, inject into the preheated tire mold, and close the mold for later use;

[0028] S5. Low-pressure pre-dispersion treatment: Maintain a constant temperature throughout the mold cavity, apply constant static pressure to the mold cavity and hold the pressure;

[0029] S6. Gradient cross-linking foaming: The process involves a three-stage gradient heating process, which proceeds sequentially through three stages: low-temperature heat preservation reaction, medium-high temperature cross-linking foaming, and slow cooling and shaping.

[0030] S7. Demolding and Curing: The tire blank is removed from the mold and transferred to a constant temperature environment for curing treatment to obtain the wear-resistant polyurethane tire product.

[0031] By adopting the above technical solutions, S1 removes the free moisture adsorbed on the surface and in the pores of the filler through vacuum heating and drying, avoiding the reaction of residual moisture with isocyanate during casting to generate carbon dioxide bubbles, which could lead to pinholes or honeycomb defects in the matrix. S2 adopts a step-by-step feeding strategy, first fully wetting and pre-dispersing the covalent hybrid reinforcing filler in a polyol matrix, so that the surface of the filler particles is coated with polyol, then adding the remaining functional components for further dispersion, and finally adding the compound foaming system for brief mixing, avoiding premature escape of the foaming agent and uneven dispersion caused by one-time mixing of the components. S3 reduces the viscosity of the prepolymer by preheating and vacuum degassing, improving flowability and metering accuracy. S4 fully homogenizes components A and B in a short time under high-speed shearing, and starts the cross-linking foaming reaction after being injected into the preheated mold. S5 applies low-pressure static pressure and maintains constant temperature in the early stage of the cross-linking reaction, using static pressure to suppress the sedimentation of high-density filler in the low-viscosity liquid system, while allowing residual micro-bubbles in the liquid to slowly float to the surface and be discharged under pressure, providing a reaction matrix with uniform component distribution and no macroscopic bubble defects for subsequent cross-linking. S6 separates the three physicochemical processes—interfacial grafting, cross-linking foaming, and internal stress relaxation—on a time axis through a three-stage gradient heating process: the low-temperature stage completes the interfacial covalent grafting of the silane coupling agent and the polyol hydroxyl groups, as well as the ordered pre-arrangement of the dynamic bond network; the medium-high temperature stage completes the cross-linking of the polyurethane matrix and the shaping of the cell structure; and the slow cooling stage allows the molecular chain conformation to fully relax through gradual cooling, eliminating the internal stress accumulated during the molding process. S7 provides sufficient time for the reversible bonds in the dynamic cross-linking network to reach final structural equilibrium through isothermal curing, resulting in a tire product with stable performance.

[0032] Preferably, in step S2, the vacuum degree of the vacuum degassing is -0.08MPa to -0.1MPa, the degassing time is 35min to 45min, and the system temperature is maintained after degassing is completed for later use.

[0033] By adopting the above technical solution, continuous degassing under a suitable vacuum can effectively extract dissolved gas and microbubbles introduced during the stirring process of component A. After degassing, the system temperature is maintained to keep the liquid at a stable viscosity and fluidity, ensuring accurate metering and stable reaction when mixed with component B, and avoiding the occurrence of porosity defects in the finished product due to residual bubbles.

[0034] Preferably, in step S6, the three-stage gradient heating program specifically comprises:

[0035] The first stage of the low-temperature holding reaction involves heating to 60°C to 70°C at a rate of 0.8°C / min to 1.2°C / min and holding for 1.5 to 2.5 hours.

[0036] The second stage involves high-temperature cross-linking foaming, with the temperature increased to 105℃ to 115℃ at a rate of 1.2℃ / min to 1.8℃ / min, and held at that temperature for 5h to 7h.

[0037] The third stage involves slow cooling and shaping, with the temperature decreasing to 35°C to 45°C at a rate of 0.4°C / min to 0.6°C / min.

[0038] By adopting the above technical solution, the first stage of low-temperature insulation reaction uses a low heating rate, maintaining the temperature above the boiling point of cyclopentane. This allows cyclopentane to vaporize smoothly and form pores without violent boiling that could lead to pore merging. Simultaneously, it provides sufficient time and a mild thermodynamic environment for the interfacial grafting reaction between the epoxy silane coupling agent and the polyol hydroxyl groups, as well as the orderly arrangement of dynamic bonds. In the second stage of medium-high temperature cross-linking foaming, the gelation reaction between isocyanate and polyol and the chemical foaming reaction between isocyanate and water occur simultaneously. The polyurethane main network is fully cross-linked, the microporous structure is stabilized, and the slow-release interface repair microspheres degrade under heat within this temperature range, releasing the coupling agent to complete interface repair. The third stage of slow cooling and shaping uses a low cooling rate to gradually cool the product. The molecular chain conformation fully relaxes during cooling, avoiding excessive temperature differences between the inside and outside of the matrix caused by rapid cooling, which can generate thermal stress and microcracks, thus stabilizing the product's dimensions and performance.

[0039] Preferably, in the second stage of high-temperature cross-linking foaming, the corresponding area of ​​the tire tread is heated so that the temperature of the tire tread area is 10°C to 15°C higher than that of the tire body area.

[0040] By adopting the above technical solution, in the second stage of high-temperature cross-linking foaming, the tread area is directionally heated by the mold tread side heating module, forming a temperature gradient that decreases from the tread to the tire body. Covalently hybridized reinforcing filler particles and dynamic cross-linked components migrate to the high-temperature area under thermodynamic drive, forming a gradient structure enriched with functional components in the shallow surface layer of the tread. The tread area has a higher filler density and cross-linking density, resulting in high wear resistance, while the tire body area maintains a lower filler content and cross-linking density, resulting in high elasticity and good cushioning performance. This achieves a gradient tire with a natural radial transition of material properties obtained by one-step casting.

[0041] Preferably, in step S6, the heating rate and the holding time at each stage are adjusted according to the exothermic reaction rate of the material in the mold.

[0042] During the medium- and high-temperature cross-linking and foaming stage, the slow-release interface repair microspheres release the silane coupling agent encapsulated inside when heated.

[0043] By adopting the above technical solution, an online infrared temperature control system is used to monitor the heat release rate of the material reaction in the mold cavity in real time. When the heat release rate exceeds the preset threshold, the heating power is automatically reduced and the holding time is extended to prevent localized explosive polymerization that leads to uneven crosslinking density. When the heat release rate is lower than the preset value, the heating rate is appropriately increased to shorten the molding cycle, thus achieving dynamic and precise control of the crosslinking foaming process. During the medium- and high-temperature crosslinking foaming stage, the sustained-release interface repair microspheres are heated, causing the polylactic acid shell to degrade and releasing γ-glycidyl etheroxypropyltrimethoxysilane, which diffuses to the filler-matrix interface region. Its epoxy groups undergo ring-opening reaction with the residual phenolic hydroxyl groups of lignin, and after methoxyl hydrolysis, it condenses with the silanol groups on the surface of nano-silica, performing secondary covalent repair on the weak points of the interface bonding, making the filler-matrix interface bonding more complete and uniform under high filler content.

[0044] Preferably, in step S7, the temperature of the aging process is 40°C to 50°C, and the aging time is 10h to 14h.

[0045] By adopting the above technical solution, sufficient time is provided for curing under suitable constant temperature conditions to allow enough time for the conformational adjustment of hindered urea covalent bonds, the orderly arrangement of urea supramolecular hydrogen bonds, and the stabilization of metal coordination bonds in the graded dynamic chain extender. This allows the dynamic auxiliary network to reach a thermodynamically stable state, ensuring that the tire has stable dimensions and performance before being put into use, and avoiding performance fluctuations in the initial use stage caused by insufficient curing.

[0046] In summary, this application has the following beneficial effects:

[0047] 1. Since this application uses bio-based polyether polyol as the matrix, combined with covalent hybrid reinforcing filler and hierarchical dynamic chain extension system, and with metal coordination crosslinking aid to construct a two-level crosslinking network, the interface bonding between the filler and the matrix is ​​strengthened by covalent bonds, and the alternating stress is dissipated in an orderly manner by relying on hierarchical bond energy. While maintaining the basic load-bearing capacity, the wear resistance and crack propagation resistance of the material are improved, and the heat generation performance under dynamic load is improved.

[0048] 2. In this application, polylactic acid slow-release microspheres are preferably coated with silane coupling agents and combined with surface-modified solid lubricating fillers. Since the microspheres can gradually release functional components during the cross-linking high-temperature stage, they can specifically repair weak areas at the interface. The lubricating fillers can reduce micro-abrasive wear. The two work together to improve the uniformity of the interface bonding and the long-term stability of wear resistance.

[0049] 3. The method of this application completes the interfacial covalent grafting, main body cross-linking foaming and slow cooling shaping in stages through a three-stage gradient heating cross-linking foaming process, so that the interfacial reaction and the matrix cross-linking process are matched in time, which can effectively reduce the residual internal stress inside the product and improve the uniformity of the cross-linking network and the stability of the finished product performance.

[0050] 4. The method of this application, by differentially heating the tread area during the medium-high temperature cross-linking foaming stage, uses the temperature gradient to induce functional components to migrate and accumulate to the tread surface, and can form a gradient structure with high surface reinforcement and high tire resilience in one step, avoiding the risk of interlayer delamination caused by multi-layer and multi-stage casting. Attached Figure Description

[0051] Figure 1 This is a flowchart of a method for preparing a wear-resistant polyurethane tire provided in this application;

[0052] Figure 2 These are comparison charts of Akron wear performance tests between the various embodiments and comparative examples provided in this application;

[0053] Figure 3 These are comparison diagrams of the flexural cracking performance tests of the various embodiments and comparative examples provided in this application;

[0054] Figure 4 This is a comparison chart of the compression heat generation performance tests of the various embodiments and comparative examples provided in this application. Detailed Implementation

[0055] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.

[0056] Technical Concept: Existing polyurethane tires mostly employ physical blending of fillers and single static cross-linking molding technology. The filler and polyurethane matrix only have a physical bond, resulting in low interfacial bonding strength and insufficient compatibility, easily leading to interfacial defects and stress concentration. Simultaneously, traditional single cross-linking networks lack stress self-adaptive dissipation capabilities, making tires prone to microcrack initiation and continuous propagation under long-term heavy-load alternating conditions. The internal heat generated during dynamic friction is also significant, resulting in obvious shortcomings in the wear resistance and fatigue resistance of traditional polyurethane tires, making them unsuitable for high-intensity, long-cycle industrial operating conditions.

[0057] This technical solution employs a bio-based polyether polyol composite formulation system, introducing covalently hybrid reinforcing fillers to construct a stable chemical bonding interface. It combines compounded hierarchical dynamic chain extenders and metal coordination agents to form a multi-level cross-linked network. Simultaneously, it is supplemented with slow-release interface repair microspheres and solid lubricating fillers for synergistic modification. Furthermore, it adopts a segmented gradient temperature cross-linking process and a differentiated temperature-controlled molding process for the tread. From multiple dimensions such as interface reinforcement, network structure optimization, defect repair, and molding process control, it effectively solves the technical problems of weak interface bonding, insufficient stress dissipation capacity, poor wear and fatigue resistance, and high dynamic heat generation in traditional products.

[0058] Preparation Example 1: Preparation of Covalent Hybrid Reinforcing Filler: 30 parts by weight of alkali lignin were added to a 5% sodium hydroxide aqueous solution and stirred at 300 r / min until completely dissolved. The pH of the system was adjusted to 9, and the temperature was raised to 80℃. 3 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane were added dropwise at a uniform rate over 30 min. The mixture was kept at this temperature and stirred for 2 h. Then, 10 parts by weight of fumed nano-silica were added, and the mixture was kept at this temperature and stirred for another 3 h. Finally, 2 parts by weight of the alkali lignin were added. After dispersing phenol-inhibiting antioxidant 1010 by stirring for 1 hour, the pH of the system was adjusted to 7 with dilute hydrochloric acid. After filtration, the filter cake was washed with deionized water until neutral. The filter cake was then dried in a vacuum oven at 105℃ for 12 hours. After removal, it was pulverized by an air jet mill to an average particle size of 200 nm to obtain hybrid filler. The silane grafting rate of the product was determined to be 8.2% after extraction with toluene Soxhlet extraction for 24 hours. The silica loading was determined to be 24.7% by the loss on ignition method after calcination at 800℃ for 2 hours.

[0059] Preparation Example 2: Preparation of graded dynamic chain extender: 10 parts by weight of N,N'-bis(2-hydroxyethyl)urea were added to a sealed reactor with a stirrer. Dry nitrogen was purged throughout the process for protection. The mixture was heated to 65°C and stirred until completely melted. Then, 20 parts by weight of N,N'-di-tert-butylethylenediamine were added. The mixture was kept at this temperature and stirred at 150 r / min for 40 min until the system was homogeneous. The mixture was then allowed to cool naturally to room temperature at a rate of 1°C / min before being discharged to obtain the graded dynamic chain extender. The hydroxyl value of the product was determined three times in parallel using the phthalic anhydride esterification method, and the average value was taken. The value was 452 mg KOH / g.

[0060] Preparation Example 3: Preparation of Sustained-Release Interface Repair Microspheres: The microspheres were prepared using an oil-in-water solvent evaporation method. 5 parts by weight of polylactic acid and 2 parts by weight of γ-glycidyl etheroxypropyltrimethoxysilane were added to 20 parts by weight of dichloromethane and stirred at room temperature until completely dissolved to obtain an oil phase. Separately, 1 part by weight of polyvinyl alcohol was added to 100 parts by weight of deionized water and stirred until dissolved to obtain a 1% aqueous phase. Under constant temperature conditions of 25°C, the oil phase was slowly added dropwise to the aqueous phase at a rate of 1 drop / second at a flow rate of 8000 r / min. After emulsification at high speed for 30 min, the solvent was evaporated by stirring at atmospheric pressure to 40℃ for 6 h. The precipitate was collected by centrifugation at 6000 r / min for 10 min, washed three times with deionized water, and then freeze-dried under vacuum at -50℃ for 24 h to obtain polylactic acid sustained-release microspheres. After extraction of free silane with methanol, the encapsulation efficiency of the silane coupling agent was calculated to be 72.3% by ultraviolet spectrophotometry at a wavelength of 220 nm. The average particle size of the product was measured to be 20 μm by laser particle size analyzer.

[0061] Preparation Example 4: Preparation of Compound Foaming System: A stirring container with a sealed lid was pre-cooled to 10°C. 1 part by weight of deionized water and 2 parts by weight of cyclopentane were added to the container sequentially. The mixture was stirred at 200 r / min for 20 min at 25°C and normal pressure until homogeneous. After sealing, the mixture was stored at 5°C to obtain the compound foaming system. The density was measured three times in parallel using the density bottle method in a constant temperature water bath at 25°C. The average value was taken to obtain a system density of 0.76 g / cm³, and the relative deviation of the three measurements was 0.32%.

[0062] Preparation Example 5: Preparation of oleic acid-coated molybdenum disulfide nanoparticles: 10 parts by weight of molybdenum disulfide powder with an average particle size of 50 nm were added to 80 parts by weight of anhydrous ethanol and ultrasonically dispersed at 300 W for 20 min to obtain a uniform suspension. The suspension was transferred to a reaction vessel and heated to 60 °C. 1.5 parts by weight of oleic acid were added dropwise at a uniform rate over 20 min. The mixture was kept at this temperature and stirred for 2 h. After the reaction was completed, the mixture was centrifuged at 5000 r / min for 15 min to separate the particles. The precipitate was washed twice with anhydrous ethanol and dried in a vacuum oven at 80 °C for 8 h to obtain oleic acid-coated molybdenum disulfide nanoparticles. Thermogravimetric analysis was performed under a nitrogen atmosphere at a temperature of 10 °C / min to 600 °C. The oleic acid coating rate of the product was determined to be 6.8%, and the activation index of the product was determined to be 94.2% by liquid paraffin precipitation method.

[0063] The following are the main raw materials and reagents used in the preparation examples, embodiments, and comparative examples, and their sources and specifications are as follows; unless otherwise specified, all reagents are commercially available analytical grade or higher products:

[0064] 1. Alkali lignin: Purchased from: Sigma-Aldrich (Shanghai) Trading Co., Ltd., item number: 471003;

[0065] 2. γ-glycidoxypropyltrimethoxysilane: purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S15029;

[0066] 3. Hindered phenolic antioxidant 1010: purchased from Shanghai Linuo New Material Technology Co., Ltd., item number: 314124;

[0067] 4. N,N'-Bis(2-hydroxyethyl)urea: purchased from Wuhan Jiyesheng Chemical Co., Ltd., CAS: 15438-70-7;

[0068] 5. N,N'-Di-tert-butylethylenediamine: purchased from Tianmen Hengchang Chemical Co., Ltd., CAS: 4062-60-6;

[0069] 6. Polylactic acid: purchased from Chongqing Yusi Pharmaceutical Technology Co., Ltd., item number: YS-PLA20;

[0070] 7. Polyvinyl alcohol: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S30196;

[0071] 8. Oleic acid: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S30008;

[0072] 9. Zinc acetylacetone: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S61378;

[0073] 10. Aluminum acetylacetone: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S61350;

[0074] 11. Zirconium acetylacetonate: Purchased from Shanghai Yuanye Biotechnology Co., Ltd., product number: S43682;

[0075] 12. Bismuth neodecanoate: purchased from Tianmen Hengchang Chemical Co., Ltd., product number: HC0120;

[0076] 13. Bismuth isooctanoate: purchased from Hubei Xinjiecheng Chemical Technology Co., Ltd., CAS: 67874-71-9;

[0077] 14. 4,4'-Dicyclohexylmethane diisocyanate: purchased from Wuhan Kanos Technology Co., Ltd., item number: js2024112602;

[0078] 15. Castor oil modified polyol: purchased from Beijing Baiyuan Chemical Co., Ltd., item number: 3129.

[0079] Example 1: This example provides a wear-resistant polyurethane tire, which is made by mixing and cross-linking foaming component A (polyol composite component) and component B (isocyanate prepolymer component) at a mass ratio of 100:36.

[0080] The polyol composite component A comprises, by weight, 82.5 parts of bio-based polyether polyol matrix, 13 parts of covalent hybrid reinforcing filler, 5 parts of graded dynamic chain extender, 0.7 parts of metal coordination crosslinking aid, 0.75 parts of solid lubricating filler, 0.5 parts of slow-release interface repair microspheres, 0.4 parts of catalytic component, and 2 parts of compound foaming system.

[0081] The B isocyanate prepolymer component is an aliphatic isocyanate prepolymer.

[0082] Among them, the bio-based polyether polyol matrix is ​​castor oil modified polyol with a hydroxyl value of 340 mgKOH / g; the covalent hybrid reinforcing filler is a hindered phenol-supported silane covalently grafted lignin-nano silica hybrid filler, which is the product prepared in Preparation Example 1. It uses alkali lignin as the base and forms a Si-OC covalent bond bridging structure with fumed nano silica through an epoxy silane coupling agent. The mass ratio of alkali lignin to fumed nano silica is 3:1.

[0083] The graded dynamic chain extender is composed of N,N'-di-tert-butylethylenediamine and N,N'-di(2-hydroxyethyl)urea in a mass ratio of 2.1:1, and is the product prepared in Preparation Example 2.

[0084] Among them, the metal coordination crosslinking aid is zinc acetylacetonate; the solid lubricating filler is oleic acid-coated nano-molybdenum disulfide, which is the product prepared in Preparation Example 5; the slow-release interface repair microspheres are polylactic acid slow-release microspheres, which are the product prepared in Preparation Example 3, and are coated with γ-glycidoxypropyltrimethoxysilane inside, with an average particle size of 20 μm.

[0085] The catalytic component is bismuth neodecanoate; the compound foaming system is prepared by mixing water and cyclopentane in a mass ratio of 1:2, using the product obtained in Preparation Example 4; the aliphatic isocyanate prepolymer is a terminal isocyanate-based prepolymer obtained by reacting 4,4'-dicyclohexylmethane diisocyanate with polyether polyol, with an NCO mass fraction of 17.5%. This formulation, through the synergistic effect of covalent interfacial bonding and hierarchical dynamic crosslinking, can improve the material's crack propagation resistance while ensuring load-bearing capacity.

[0086] The above-mentioned method for preparing wear-resistant polyurethane tires includes the following steps:

[0087] S1. Drying treatment of filler: The covalent hybrid reinforcing filler is vacuum dried under heating conditions, and then sealed and stored for later use.

[0088] The drying temperature is 110℃, the vacuum degree is -0.09MPa, and the drying time is 2h, which fully removes the free moisture adsorbed on the surface of the filler and avoids pinholes and bubbles after molding.

[0089] S2 and A materials are prepared by homogenization: according to the formula ratio, the bio-based polyether polyol matrix and the dried covalent hybrid reinforcing filler are pre-dispersed, then the graded dynamic chain extender, metal coordination crosslinking aid, solid lubricating filler, slow-release interface repair microspheres and catalytic components are added and dispersed until uniform. Finally, the compound foaming system is added and mixed evenly. After heating, vacuum degassing is performed and the mixture is kept warm for later use.

[0090] The pre-dispersion speed was 300 r / min and the pre-dispersion time was 12 min; the further dispersion speed was 300 r / min and the further dispersion time was 17 min; the vacuum degree of vacuum degassing was -0.09 MPa and the degassing time was 40 min. After degassing, the system temperature was maintained at 85℃ for later use.

[0091] S3, B material preheating and degassing: The aliphatic isocyanate prepolymer is preheated and stirred, and then vacuum degassed.

[0092] The preheating temperature is 47℃, the stirring speed is 200r / min, and the vacuum degassing time is 20min to ensure uniform flowability of the liquid and more stable subsequent mixing reaction.

[0093] S4. Mixing, Injection and Closing: Mix and stir the heat-insulated component A and component B according to the set mass ratio, inject into the preheated tire mold, and close the mold for later use.

[0094] The mixing speed is 1200 r / min and the mixing time is 120 s; the tire mold is a steel mold and the preheating temperature is 55 ℃.

[0095] S5. Low-pressure pre-dispersion treatment: Maintain a constant temperature throughout the mold cavity, apply constant static pressure to the mold cavity and hold the pressure.

[0096] The mold cavity has a constant temperature of 50℃ and a constant static pressure of 0.035MPa. The pressure holding time is 30min, which can suppress the sedimentation of high-density fillers and slowly discharge the trace bubbles remaining in the liquid.

[0097] S6. Gradient cross-linking foaming: The process involves a three-stage gradient heating process, which proceeds sequentially through three stages: low-temperature heat preservation reaction, medium-high temperature cross-linking foaming, and slow cooling and shaping.

[0098] The three-stage gradient heating program is as follows:

[0099] The first stage of the low-temperature holding reaction involves heating to 65°C at a rate of 1°C / min and holding for 2 hours.

[0100] The second stage involves high-temperature crosslinking and foaming, with the temperature increased to 110℃ at a rate of 1.5℃ / min and held for 6 hours. In this stage, the corresponding area of ​​the tire tread is heated, making the temperature of the tire tread area 12℃ higher than that of the tire carcass area, inducing the migration and enrichment of hybrid fillers and dynamic crosslinking components to the surface of the tire tread. During the process, the heating rate and the holding time of each stage are adjusted according to the exothermic reaction rate of the in-mold material to ensure precise matching of the three stages of interface grafting, crosslinking, and foaming. At the same time, the interface repair microspheres release the silane coupling agent inside when heated, which repairs the weak areas of the interface between the filler and the matrix.

[0101] The third stage involves slow cooling and shaping, with the temperature decreasing to 40℃ at a rate of 0.5℃ / min.

[0102] S7. Demolding and Curing: The tire blank is removed from the mold and transferred to a constant temperature environment for curing treatment to obtain the wear-resistant polyurethane tire product.

[0103] The curing process involves a temperature of 45℃ and a curing time of 12 hours, which allows the dynamic cross-linked network to gradually achieve structural stability and improves the dimensional consistency and performance uniformity of the finished product.

[0104] Example 2: This example provides a wear-resistant polyurethane tire, which is made by mixing and cross-linking foaming component A (polyol composite component) and component B (isocyanate prepolymer component) at a mass ratio of 100:32.

[0105] The polyol composite component A comprises, by weight, 75 parts of bio-based polyether polyol matrix, 8 parts of covalent hybrid reinforcing filler, 3 parts of graded dynamic chain extender, 0.4 parts of metal coordination crosslinking aid, 0.3 parts of solid lubricating filler, 0.2 parts of slow-release interface repair microspheres, 0.2 parts of catalytic component, and 1 part of compound foaming system.

[0106] The B isocyanate prepolymer component is an aliphatic isocyanate prepolymer.

[0107] Among them, the bio-based polyether polyol matrix is ​​castor oil modified polyol with a hydroxyl value of 320 mgKOH / g; the covalent hybrid reinforcing filler is a hindered phenol-supported silane covalently grafted lignin-nano silica hybrid filler, which is the product prepared in Preparation Example 1. It uses alkali lignin as the base and forms a Si-OC covalent bond bridge structure with fumed nano silica through an epoxy silane coupling agent. The mass ratio of alkali lignin to fumed nano silica is 2:1.

[0108] The graded dynamic chain extender is composed of N,N'-di-tert-butylethylenediamine and N,N'-di(2-hydroxyethyl)urea in a mass ratio of 2:1, and is the product obtained in Preparation Example 2.

[0109] Among them, the metal coordination crosslinking aid is zinc acetylacetonate; the solid lubricating filler is oleic acid-coated nano-molybdenum disulfide, which is the product prepared in Preparation Example 5; the slow-release interface repair microspheres are polylactic acid slow-release microspheres, which are the product prepared in Preparation Example 3, and are coated with γ-glycidyl etheroxypropyltrimethoxysilane, with an average particle size of 10 μm.

[0110] The catalytic component is bismuth neodecanoate; the compound foaming system is prepared by mixing water and cyclopentane at a mass ratio of 1:2, using the product obtained in Preparation Example 4; the aliphatic isocyanate prepolymer is a terminal isocyanate-based prepolymer obtained by reacting 4,4'-dicyclohexylmethane diisocyanate with polyether polyol, with an NCO mass fraction of 16%. The system exhibits better flowability at low filler content, making it suitable for the molding requirements of thin-walled, small tires.

[0111] The above-mentioned method for preparing wear-resistant polyurethane tires includes the following steps:

[0112] S1. Drying treatment of filler: The covalent hybrid reinforcing filler is vacuum dried under heating conditions, and then sealed and stored for later use.

[0113] The drying temperature was 105℃, the vacuum degree was -0.08MPa, and the drying time was 1.5h, which fully removed the free moisture adsorbed on the surface of the filler.

[0114] S2 and A materials are prepared by homogenization: according to the formula ratio, the bio-based polyether polyol matrix and the dried covalent hybrid reinforcing filler are pre-dispersed, then the graded dynamic chain extender, metal coordination crosslinking aid, solid lubricating filler, slow-release interface repair microspheres and catalytic components are added and dispersed until uniform. Finally, the compound foaming system is added and mixed evenly. After heating, vacuum degassing is performed and the mixture is kept warm for later use.

[0115] The pre-dispersion speed was 250 r / min and the pre-dispersion time was 10 min; the further dispersion speed was 250 r / min and the further dispersion time was 15 min; the vacuum degree of vacuum degassing was -0.08 MPa and the degassing time was 35 min. After degassing, the system temperature was maintained at 80℃ for later use.

[0116] S3, B material preheating and degassing: The aliphatic isocyanate prepolymer is preheated and stirred, and then vacuum degassed.

[0117] The preheating temperature is 45℃, the stirring speed is 180r / min, and the vacuum degassing time is 15min to ensure that the liquid has stable casting fluidity.

[0118] S4. Mixing, Injection and Closing: Mix and stir the heat-insulated component A and component B according to the set mass ratio, inject into the preheated tire mold, and close the mold for later use.

[0119] The mixing speed is 1000 r / min and the mixing time is 100 s; the tire mold is a steel mold and the preheating temperature is 50 ℃.

[0120] S5. Low-pressure pre-dispersion treatment: Maintain a constant temperature throughout the mold cavity, apply constant static pressure to the mold cavity and hold the pressure.

[0121] The mold cavity maintains a constant temperature of 48℃, a constant static pressure of 0.02MPa, and a pressure holding time of 25min to remove residual air bubbles from the liquid and ensure uniform distribution of the filler.

[0122] S6. Gradient cross-linking foaming: The process involves a three-stage gradient heating process, which proceeds sequentially through three stages: low-temperature heat preservation reaction, medium-high temperature cross-linking foaming, and slow cooling and shaping.

[0123] The three-stage gradient heating program is as follows:

[0124] The first stage of the low-temperature holding reaction involves heating to 60℃ at a rate of 0.8℃ / min and holding for 1.5 hours.

[0125] The second stage involves high-temperature cross-linking foaming, with the temperature increased to 105℃ at a rate of 1.2℃ / min and held for 5 hours. During this stage, the corresponding area of ​​the tire tread is heated, making the temperature of the tire tread area 10℃ higher than that of the tire carcass area, inducing the migration and enrichment of hybrid fillers and dynamic cross-linking components to the surface of the tire tread. During the process, the heating rate and the holding time of each stage are adjusted according to the exothermic reaction rate of the in-mold materials to ensure the smooth progress of the reaction in each stage. At the same time, the slow-release interface repair microspheres release the silane coupling agent encapsulated inside when heated, repairing the weak areas of the interface bonding.

[0126] The third stage involves slow cooling and shaping, with the temperature decreasing to 35℃ at a rate of 0.4℃ / min.

[0127] S7. Demolding and Curing: The tire blank is removed from the mold and transferred to a constant temperature environment for curing treatment to obtain the wear-resistant polyurethane tire product.

[0128] The curing temperature is 40℃ and the curing time is 10h, which makes the cross-linked network fully stable and ensures the basic mechanical properties of the finished product.

[0129] Example 3: This example provides a wear-resistant polyurethane tire, which is made by mixing and cross-linking foaming component A (polyol composite component) and component B (isocyanate prepolymer component) at a mass ratio of 100:40.

[0130] The polyol composite component A comprises, by weight, 90 parts of bio-based polyether polyol matrix, 18 parts of covalent hybrid reinforcing filler, 7 parts of graded dynamic chain extender, 1.0 part of metal coordination crosslinking aid, 1.2 parts of solid lubricating filler, 0.8 parts of slow-release interface repair microspheres, 0.6 parts of catalytic component, and 3 parts of compound foaming system.

[0131] The B isocyanate prepolymer component is an aliphatic isocyanate prepolymer.

[0132] Among them, the bio-based polyether polyol matrix is ​​castor oil modified polyol with a hydroxyl value of 360 mg KOH / g; the covalent hybrid reinforcing filler is a hindered phenol-supported silane covalently grafted lignin-nano silica hybrid filler, which is the product prepared in Preparation Example 1. It uses alkali lignin as the base and forms a Si-OC covalent bond bridging structure with fumed nano silica through an epoxy silane coupling agent. The mass ratio of alkali lignin to fumed nano silica is 4:1.

[0133] The graded dynamic chain extender is composed of N,N'-di-tert-butylethylenediamine and N,N'-di(2-hydroxyethyl)urea in a mass ratio of 2.2:1, and is the product prepared in Preparation Example 2.

[0134] Among them, the metal coordination crosslinking aid is zinc acetylacetonate; the solid lubricating filler is oleic acid-coated nano-molybdenum disulfide, which is the product prepared in Preparation Example 5; the slow-release interface repair microspheres are polylactic acid slow-release microspheres, which are the product prepared in Preparation Example 3, and are coated with γ-glycidyl etheroxypropyltrimethoxysilane, with an average particle size of 30 μm.

[0135] The catalytic component is bismuth neodecanoate; the compound foaming system is prepared by mixing water and cyclopentane in a mass ratio of 1:2, using the product obtained in Preparation Example 4; the aliphatic isocyanate prepolymer is a terminal isocyanate prepolymer prepared by reacting 4,4'-dicyclohexylmethane diisocyanate with polyether polyol, with an NCO mass fraction of 19%. The combination of high filler and high crosslinking density can further improve the wear resistance of the tread and meet the needs of heavy-duty operating conditions.

[0136] The above-mentioned method for preparing wear-resistant polyurethane tires includes the following steps:

[0137] S1. Drying treatment of filler: The covalent hybrid reinforcing filler is vacuum dried under heating conditions, and then sealed and stored for later use.

[0138] The drying temperature is 115℃, the vacuum degree is -0.1MPa, and the drying time is 2.5h, which completely removes the adsorbed moisture in the pores of the filler and avoids bubble defects in the high filler system.

[0139] S2 and A materials are prepared by homogenization: according to the formula ratio, the bio-based polyether polyol matrix and the dried covalent hybrid reinforcing filler are pre-dispersed, then the graded dynamic chain extender, metal coordination crosslinking aid, solid lubricating filler, slow-release interface repair microspheres and catalytic components are added and dispersed until uniform. Finally, the compound foaming system is added and mixed evenly. After heating, vacuum degassing is performed and the mixture is kept warm for later use.

[0140] The pre-dispersion speed was 350 r / min and the pre-dispersion time was 15 min; the further dispersion speed was 350 r / min and the further dispersion time was 20 min; the vacuum degree of vacuum degassing was -0.1 MPa and the degassing time was 45 min. After degassing, the system temperature was maintained at 90℃ for later use.

[0141] S3, B material preheating and degassing: The aliphatic isocyanate prepolymer is preheated and stirred, and then vacuum degassed.

[0142] The preheating temperature is 50℃, the stirring speed is 220r / min, and the vacuum degassing time is 25min to reduce the viscosity of the prepolymer and ensure uniform mixing.

[0143] S4. Mixing, Injection and Closing: Mix and stir the heat-insulated component A and component B according to the set mass ratio, inject into the preheated tire mold, and close the mold for later use.

[0144] The mixing speed is 1400 r / min and the mixing time is 140 s; the tire mold is a steel mold and the preheating temperature is 60 ℃.

[0145] S5. Low-pressure pre-dispersion treatment: Maintain a constant temperature throughout the mold cavity, apply constant static pressure to the mold cavity and hold the pressure.

[0146] The mold cavity is kept at a constant temperature of 52℃, a constant static pressure of 0.05MPa, and a holding time of 35min to suppress the sedimentation tendency of high-content fillers and ensure the uniformity of the system.

[0147] S6. Gradient cross-linking foaming: The process involves a three-stage gradient heating process, which proceeds sequentially through three stages: low-temperature heat preservation reaction, medium-high temperature cross-linking foaming, and slow cooling and shaping.

[0148] The three-stage gradient heating program is as follows:

[0149] The first stage of the low-temperature holding reaction involves heating to 70℃ at a rate of 1.2℃ / min and holding for 2.5 hours.

[0150] The second stage involves high-temperature cross-linking foaming, with the temperature increased to 115℃ at a rate of 1.8℃ / min and held for 7 hours. This stage heats the corresponding area of ​​the tread, making the temperature of the tread area 15℃ higher than that of the carcass area, thereby enhancing the migration and enrichment of functional components to the tread surface. During the process, the heating rate and the holding time of each stage are adjusted according to the exothermic reaction rate of the in-mold material to avoid localized bursting and internal stress. At the same time, the slow-release interface repair microspheres fully release the silane coupling agent encapsulated inside when heated, comprehensively repairing the weak interface areas of the high-filler system.

[0151] The third stage involves slow cooling and shaping, with the temperature decreasing to 45℃ at a rate of 0.6℃ / min.

[0152] S7. Demolding and Curing: The tire blank is removed from the mold and transferred to a constant temperature environment for curing treatment to obtain the wear-resistant polyurethane tire product.

[0153] The curing process involves a curing temperature of 50℃ and a curing time of 14 hours, which fully perfects the network structure of the high cross-linking density system and ensures that the mechanical properties and wear resistance of the finished product meet the standards.

[0154] Comparative Example 1: The only difference between this comparative example and Example 1 is that the covalent hybrid reinforcing filler is replaced with an equal mass of physically mixed filler, which is obtained by mechanically mixing alkali lignin and fumed nano silica at a mass ratio of 3:1. At the same time, an antioxidant 1010 with an equal amount of hindered phenol as the covalent hybrid reinforcing filler in Example 1 is added directly into component A without silane covalent grafting or in-situ loading of hindered phenol. The remaining raw material ratios, preparation process steps and parameters are completely consistent with those of Example 1.

[0155] Comparative Example 2: The only difference between this comparative example and Example 1 is that the graded dynamic chain extender is replaced with an equal mass of 1,4-butanediol; the other raw material ratios, preparation process steps and parameters are completely consistent with Example 1.

[0156] Comparative Example 3: The only difference between this comparative example and Example 1 is that the polylactic acid sustained-release microspheres were removed, and instead, γ-glycidyl etheroxypropyltrimethoxysilane of the same mass as the silane coupling agent inside the sustained-release microspheres in Example 1 was directly added during the homogenization preparation stage of material A; the remaining raw material ratios, preparation process steps and parameters are completely consistent with those of Example 1.

[0157] Comparative Example 4: The only difference between this comparative example and Example 1 is that the three-stage gradient heating process in the S6 gradient crosslinking foaming is cancelled, and the mold is directly vulcanized at a constant temperature of 110°C for 8 hours after molding. The total vulcanization holding time is the same as the total holding time of the three-stage process in Example 1. The other raw material ratios, other process steps and parameters are completely the same as those in Example 1.

[0158] Comparative Example 5: The only difference between this comparative example and Example 1 is that: in the high-temperature cross-linking foaming stage of S6, the tread zone heating is not activated, and the mold cavity is kept at a uniform constant temperature of 110°C throughout; the remaining raw material ratios, remaining process steps and parameters are completely consistent with Example 1.

[0159] Comparative Example 6: This comparative example adopts a polyurethane solid tire technology solution commonly used in the art: the formulation consists of a polyol component A and an isocyanate prepolymer component B. Component A, by weight, includes 100 parts polyester polyol, 15 parts carbon black N330, 8 parts 1,4-butanediol, 0.3 parts organic bismuth catalyst, and 1 part water; component B is an MDI prepolymer with an NCO mass fraction of 18%; components A and B are mixed at a mass ratio of 100:35. The preparation process includes: after mixing the raw materials, injecting them into a mold preheated to 55°C, constant-temperature vulcanization at 110°C for 8 hours, natural cooling and demolding, and curing at 45°C for 12 hours. This comparative example does not add covalent hybrid reinforcing fillers, graded dynamic chain extenders, slow-release interface repair microspheres, or oleic acid-coated nano-molybdenum disulfide, and does not include low-pressure pre-dispersion, three-stage gradient heating, or tread zone differentiated heating steps. All other performance test conditions are completely consistent with those of Example 1.

[0160] I. Akron abrasion performance test: The test was conducted in accordance with GB / T1689-2014 "Determination of abrasion resistance of vulcanized rubber or thermoplastic rubber (Akron abrasion tester method)". Before the test, all samples were placed in a standard environment at 23°C and 50% relative humidity for 24 hours to condition. Rectangular samples with dimensions of 12mm×12mm×30mm were cut from the working area of ​​the finished tire tread of Examples 1 to 3 and Comparative Examples 1 to 6. Five parallel samples were prepared for each group. 180-mesh alumina sandpaper was used for the test. After each group of tests was completed, a brand new sandpaper was used to ensure consistent abrasion conditions. The sample was fixed to the surface of the rubber wheel of the testing machine, and a vertical load of 19.6 N was applied. The grinding wheel speed was set to 76 r / min and the sample inclination angle was 15°. The sample was first pre-ground at 1000 rpm. After cleaning the surface debris, the initial mass was weighed and recorded. Then, the sample was subjected to formal grinding at 3400 rpm. After the test, the remaining mass of the sample was weighed again. The grinding volume was calculated by combining the sample density. After removing abnormal data with a deviation of more than 10%, the average grinding volume of each group was taken to characterize the wear resistance of the material.

[0161] II. Flexural cracking performance test: The test was conducted in accordance with GB / T13934-2006 "Determination of Flexural Cracking of Vulcanized Rubber or Thermoplastic Rubber". The test was carried out in a standard laboratory environment at 23℃. Type I unnotched dumbbell specimens conforming to standard dimensions were cut from the tread of finished tires from Examples 1 to 3 and Comparative Examples 1 to 6. Five parallel specimens were prepared for each group. The specimens were clamped flat at both ends on the fixtures of the flexural testing machine. The initial spacing of the fixtures was adjusted to 20 mm, the flexural frequency was set to 300 cycles / min, and the flexural angle was set to 45°. After starting the equipment, the machine was stopped every 50,000 cycles to observe the surface condition of the specimens. The number of flexural cycles when the first visible crack appeared was recorded. The test continued until the crack length reached 1 mm, and the corresponding number of flexural cycles was recorded. The arithmetic mean of the two values ​​for each group of specimens was taken to characterize the material's resistance to crack propagation and fatigue performance.

[0162] III. Compression Heat Generation Performance Test: The test was conducted in accordance with GB / T1687.1-2016 "Determination of Temperature Rise and Fatigue Resistance of Vulcanized Rubber in Flexural Test - Part 1: Basic Principles". Before testing, all samples were placed in a 25°C environment for 12 hours. Cylindrical samples with a diameter of 17.8 mm and a height of 25 mm were cut from the carcass of finished tires from Examples 1 to 3 and Comparative Examples 1 to 6. Five parallel samples were prepared for each group. The samples were placed vertically between the upper and lower constant-temperature plates of the compression heat generation testing machine. A static compression preload of 2 MPa was applied, with a stroke set to 4.45 mm and a vibration frequency of 30 Hz. The initial temperature of the test chamber was stabilized at 25°C. After the equipment ran continuously for 25 minutes, it was stopped, and a temperature probe was immediately inserted to measure the core temperature of the sample. The difference between the final core temperature and the initial temperature was calculated, i.e., the temperature rise. After removing abnormal data, the average temperature rise value for each group was taken to characterize the internal heat generation level of the material under dynamic load.

[0163] Table 1: Key Performance Test Results of Each Embodiment and Comparative Example

[0164]

[0165] Note 1: All data in the table are the arithmetic mean of the test results of 5 parallel samples in each group. Abnormal data with a relative deviation of more than 10% were removed before calculation.

[0166] 2. The smaller the Akron wear volume value, the better the wear resistance of the material; the larger the average number of flexural cracks, the better the crack propagation resistance and fatigue resistance of the material; the smaller the compression heat generation temperature rise value, the lower the endogenous heat level of the material under dynamic load.

[0167] 3. All samples were taken from the designated parts of the corresponding finished tires. Wear and flexural test samples were taken from the working area of ​​the tread, and compression heat test samples were taken from the tire body. Before testing, the environmental conditions were strictly conditioned according to the corresponding standard. The test environment temperature was 23℃.

[0168] As can be seen from Examples 1-3 and Comparative Example 1, and Table 1, the hybrid reinforcing filler with silane covalent grafting and in-situ loading of hindered phenol can significantly enhance the interfacial bonding strength between the filler and the matrix, optimize stress transfer efficiency, reduce filler agglomeration and interfacial peeling defects, and improve the long-term effect of antioxidant components, thus simultaneously improving the wear resistance, crack propagation resistance and dynamic heat generation performance of the material.

[0169] As can be seen from Examples 1-3 and Comparative Example 2, and Table 1, the hierarchical bond energy crosslinking system constructed by introducing a hierarchical dynamic chain extender, compared with the fixed crosslinking network formed by ordinary diol chain extension, can dissipate external force energy through the reversible breaking and rearrangement of dynamic bonds when the material is subjected to alternating stress, delay the initiation and propagation of microcracks, effectively improve the flexural fatigue resistance of the material, and also have a positive auxiliary effect on wear resistance and heat generation control.

[0170] As can be seen from Examples 1-3 and Comparative Example 3, and Table 1, the slow-release interface repair method using polylactic acid microspheres coated with silane coupling agents, compared to the method of adding silane coupling agents directly at one time, can gradually release functional components during the medium and high temperature stages of the crosslinking reaction, specifically repairing local weak areas at the interface between the filler and the matrix, improving the uniformity of interface bonding and the integrity of the overall network, thereby optimizing the mechanical stability and wear resistance of the material.

[0171] As can be seen from Examples 1-3 and Comparative Example 4, and Table 1, the three-stage gradient heating crosslinking foaming process, compared with the one-step isothermal vulcanization process, can achieve sequential matching of the interfacial covalent grafting reaction and the main crosslinking foaming reaction, allowing the filler interface bonding and matrix network construction to proceed fully, while reducing residual internal stress in the product, improving the uniformity of the crosslinking network, and ultimately improving the wear resistance and flexural strength of the material.

[0172] As can be seen from Examples 1-3 and Comparative Example 5, and Table 1, differential heating of the tread area during the crosslinking foaming stage creates a temperature gradient. Compared with uniform heating of the entire mold cavity, this can induce hybrid fillers and dynamic crosslinking components to migrate and accumulate directionally to the tread surface, forming a gradient structure with high surface reinforcement and repair, and high tire resilience in situ. This enhances the wear resistance and crack resistance of the tread while ensuring the elasticity of the tire body.

[0173] As can be seen from Examples 1-3 and Comparative Example 6, and Table 1, the complete technical solution of the composite filler system, hierarchical dynamic crosslinking design and gradient molding process of this application can achieve simultaneous improvement in multiple core dimensions such as wear resistance, crack propagation resistance and compression heat generation control compared with the conventional polyurethane solid tire technology solution in the field, and has a greater overall performance advantage.

[0174] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A wear-resistant polyurethane tire, characterized in that: It is made by mixing, cross-linking, foaming and curing A polyol composite component and B isocyanate prepolymer component in a mass ratio of 100:32 to 100:40; The A polyol composite component comprises, by weight, 75-90 parts of bio-based polyether polyol matrix, 8-18 parts of covalent hybrid reinforcing filler, 3-7 parts of hierarchical dynamic chain extender, 0.4-1.0 parts of metal coordination crosslinking aid, 0.3-1.2 parts of solid lubricating filler, 0.2-0.8 parts of slow-release interface repair microspheres, 0.2-0.6 parts of catalytic component, and 1-3 parts of compound foaming system; The B isocyanate prepolymer component is an aliphatic isocyanate prepolymer; The covalent hybrid reinforcing filler is a hindered phenol-supported silane covalently grafted lignin-nano silica hybrid filler. It uses alkali lignin as a base and forms a Si-OC covalent bond bridging structure with fumed nano silica through an epoxy silane coupling agent. The mass ratio of alkali lignin to fumed nano silica is 2:1 to 4:

1. The graded dynamic chain extender is a compound of N,N'-di-tert-butylethylenediamine and N,N'-di(2-hydroxyethyl)urea; The sustained-release interface repair microspheres are polylactic acid sustained-release microspheres, which are internally coated with γ-glycidoxypropyltrimethoxysilane, and the microsphere particle size is 10 μm to 30 μm.

2. The wear-resistant polyurethane tire according to claim 1, characterized in that: The metal coordination crosslinking aid is selected from at least one of zinc acetylacetonate, zirconium acetylacetonate, and aluminum acetylacetonate. The solid lubricating filler is selected from at least one of oleic acid-coated nano molybdenum disulfide and polytetrafluoroethylene micro powder. The catalytic component is an organic bismuth catalyst, selected from at least one of bismuth neodecanoate and bismuth isooctanoate; The compound foaming system is composed of water and cyclopentane; The bio-based polyether polyol matrix is ​​a castor oil-modified polyol with a hydroxyl value of 320 mg KOH / g to 360 mg KOH / g.

3. The wear-resistant polyurethane tire according to claim 1, characterized in that: The aliphatic isocyanate prepolymer is a terminal isocyanate-based prepolymer prepared by reacting 4,4'-dicyclohexylmethane diisocyanate with polyether polyol, and its NCO mass fraction is 16% to 19%.

4. A method for preparing a wear-resistant polyurethane tire, characterized in that, The method for preparing a wear-resistant polyurethane tire according to any one of claims 1-3 includes the following steps: S1. Drying treatment of filler: The covalent hybrid reinforcing filler is vacuum dried under heating conditions, and then sealed and stored for later use. S2 and A material homogenization preparation: According to the formula ratio, the bio-based polyether polyol matrix and the dried covalent hybrid reinforcing filler are pre-dispersed first, then the graded dynamic chain extender, metal coordination crosslinking aid, solid lubricating filler, slow-release interface repair microspheres and catalytic components are added and dispersed until uniform. Finally, the compound foaming system is added and mixed evenly. After heating, vacuum degassing is performed and the mixture is kept warm for later use. S3, B material preheating and degassing: The aliphatic isocyanate prepolymer is preheated and stirred, then vacuum degassed; S4. Mixing, Injection and Closing: Mix and stir the heat-insulated component A and component B according to the set mass ratio, inject into the preheated tire mold, and close the mold for later use; S5. Low-pressure pre-dispersion treatment: Maintain a constant temperature throughout the mold cavity, apply constant static pressure to the mold cavity and hold the pressure; S6. Gradient cross-linking foaming: The process involves a three-stage gradient heating process, which proceeds sequentially through three stages: low-temperature heat preservation reaction, medium-high temperature cross-linking foaming, and slow cooling and shaping. S7. Demolding and Curing: The tire blank is removed from the mold and transferred to a constant temperature environment for curing treatment to obtain the wear-resistant polyurethane tire product.

5. The method for preparing a wear-resistant polyurethane tire according to claim 4, characterized in that: In step S2, the vacuum degree of the vacuum degassing is -0.08MPa to -0.1MPa, the degassing time is 35min to 45min, and the system temperature is maintained after degassing is completed for later use.

6. The method for preparing a wear-resistant polyurethane tire according to claim 4, characterized in that: In step S6, the three-stage gradient heating program is specifically as follows: The first stage of the low-temperature holding reaction involves heating to 60°C to 70°C at a rate of 0.8°C / min to 1.2°C / min and holding for 1.5 to 2.5 hours. The second stage involves high-temperature cross-linking foaming, with the temperature increased to 105℃ to 115℃ at a rate of 1.2℃ / min to 1.8℃ / min, and held at that temperature for 5h to 7h. The third stage involves slow cooling and shaping, with the temperature decreasing to 35°C to 45°C at a rate of 0.4°C / min to 0.6°C / min.

7. The method for preparing a wear-resistant polyurethane tire according to claim 6, characterized in that: In the second stage of high-temperature cross-linking and foaming, the corresponding area of ​​the tire tread is heated so that the temperature of the tire tread area is 10°C to 15°C higher than that of the tire body area.

8. The method for preparing a wear-resistant polyurethane tire according to claim 4, characterized in that: In step S6, the heating rate and the holding time at each stage are adjusted according to the exothermic reaction rate of the material in the mold. During the medium- and high-temperature cross-linking and foaming stage, the slow-release interface repair microspheres release the silane coupling agent encapsulated inside when heated.

9. The method for preparing a wear-resistant polyurethane tire according to claim 4, characterized in that: In step S7, the temperature of the curing treatment is 40°C to 50°C, and the curing time is 10h to 14h.

Citation Information

Patent Citations

  • Heat-resistant polyurethane composition for tire filling as well as preparation method and application of heat-resistant polyurethane composition

    CN120059108A

  • Heat-resistant polyurethane composition for synthetic leather and preparation method of heat-resistant polyurethane composition

    CN121203121A